(untitled) (KYAMC Journal, 2017)
Background: With the advent of fine needle aspiration cytology (FNAC), the approach to diagnosis and management of breast lumps has been revolutionized and it has high sensitivity and specificity. Aim: In this study we analyze the spectrum of FNAC diagnoses in breast lumps and compare the diagnostic accuracy of fine FNAC in differentiating the benign and malignant lesions of breast lumps with histopathological correlation. Materials & Methods: Two years prospective study was conducted in our institution and in that 490 aspirations, including 6 bilateral were performed. Suppurative and inflammatory lesions were excluded from the total aspirates. The cytological diagnosis was classified into 3 groups benign, suspicious and malignant. After this reporting all the available 94 cases were later subjected to mastectomy or open/excision biopsy and followed-up by histopathological confirmation. Later diagnostic accuracy of cytology reporting was compared with that of histopathology. Results: A total of 490 FNAC cases were reported including 373 as benign, 4 as suspicious for carcinoma and 113 as carcinoma. Majorities were premenopausal females and commonest age group was 31-40 years. Among them only 94 cases were followed-up by histopathologic confirmation. In histopathological correlation study, we had accuracy rate of 100% for benign lesion and 92.10% for malignant lesion with false negative rate of 7.90% and false positive rate of zero with fine needle aspiration cytology in the diagnosis of palpable breast lump. The overall sensitivity of fine needle aspiration in diagnosing the palpable breast lump is 92.10%, specificity is 100%, positive predictive value is 100% and negative predictive value is 94.91%. Conclusion: FNAC in experienced hands is a very useful tool with very high specificity and rare false positive result. Sensitivity can be further improved with clinical and imaging correlation. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 780-786